2019
DOI: 10.1111/tmi.13294
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy and predictive value in differentiating the severity of dengue infection

Abstract: Objective To review the diagnostic test accuracy and predictive value of statistical models in differentiating the severity of dengue infection. Methods Electronic searches were conducted in the Cochrane Database of Systematic Reviews, Cochrane Central Register of Controlled Trials, MEDLINE (complete), PubMed and Scopus. Eligible studies to be included in this review were cohort studies with participants confirmed by laboratory test for dengue infection and comparison among the different severity of dengue inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…A systematic review of predictive tools found some have accuracy as high as 86% when applied to infection with symptom onset within 3 days and 98% for prediction of 30-day mortality. 41 Virus isolation using mammalian/mosquito cell lines or live mosquitos are definitive but labour intensive and time inefficient, and have largely been replaced by quicker, less expensive tests. 42 These novel investigations, like enzyme-linked immunosorbent assay (ELISA) against NS-1 antigen, real-time polymerase chain reaction (RT-PCR) and serology must be performed and interpreted in the context of clinical presentation, duration of symptoms, history of previous dengue infection and vaccination.…”
Section: Denguementioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of predictive tools found some have accuracy as high as 86% when applied to infection with symptom onset within 3 days and 98% for prediction of 30-day mortality. 41 Virus isolation using mammalian/mosquito cell lines or live mosquitos are definitive but labour intensive and time inefficient, and have largely been replaced by quicker, less expensive tests. 42 These novel investigations, like enzyme-linked immunosorbent assay (ELISA) against NS-1 antigen, real-time polymerase chain reaction (RT-PCR) and serology must be performed and interpreted in the context of clinical presentation, duration of symptoms, history of previous dengue infection and vaccination.…”
Section: Denguementioning
confidence: 99%
“…A systematic review of predictive tools found some have accuracy as high as 86% when applied to infection with symptom onset within 3 days and 98% for prediction of 30-day mortality. 41 …”
Section: Mosquito-borne Infections In Pregnancymentioning
confidence: 99%
“…Due to the shortcomings in implementing diagnostic tests in underdeveloped countries, recent studies in Asia and the Americas have focused on evaluating clinic variables and assigning scores depending on the frequency to establish the diagnosis (12, [21][22][23]47). Although this strategy has been helpful in improving patient care, the validation of these algorithms is a complex process due to the heterogeneity of the study population and the variability in clinical findings according to each stage of the disease (48)(49)(50)(51)(52)(53)(54)(55).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the shortcomings in implementing laboratory tests in underdeveloped countries, in the last few years, many studies in Asia and the Americas have focused on the evaluation of clinical signs or symptoms and assigning scores depending on the frequency or severity to establish the final diagnosis [12,[21][22][23]51]. Although this strategy has been helpful in the early identification of cases and improving patient care and treatment, the validation of these clinical algorithms is difficult due to the heterogeneity of the study population, the variability in the clinical presentation between countries, and the differences in the signs or symptoms according to the disease stages [52][53][54][55][56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%